Suffering bodies in 2 Maccabees 3 - Pierre J. Jordaan (In die Skriflig, 2016)
This article aims to analyse the role that bodies play in different narratives implied in 2 Maccabees 3. In order to do this, a possible dominant narrative was constructed in which the motif of suffering bodies is shown. In the same way, a challenging narrative wherein the alleviation of suffering bodies is portrayed is also revealed. Furthermore the dynamics behind these two narratives, e.g. when the Jewish deity was willing to relieve this suffering, is also investigated. It was found that the Jewish deity responds positively when his high priest and his nation are in unison apropos their worship, and are willing to counter foreign invaders of the temple and their ideologies. To come to this conclusion the narrative therapeutic approach, as used by Epston and White, was applied to 2 Maccabees 3. This approach to interpretation is quite unique.